Smart Band / Amzar Zafri Alimi, Nur Izzati Hasim … [et al.] - Alimi, AmzarZafri; Hasim, Nur Izzati; Ameruddin, Nurul Najihah; Mohd Busro, Siti Nur Syafiqah Bazila; Wan Hamdan, Wan Nurul Munirah (2018)
In this developing country, there are lot of emissions release from factories, cars and heating boilers which contain nitrogen oxides and sulphur dioxide. Due to the rainy seasons, there are high chance of rainwater to become acidic when contact with these pollutants. On the other hand, the atmospheric levels of ozone-depleting substances (ODS) rapidly increased now a days. Because of this issue there are high chance of UV ray that can penetrate through the ozone layer. After initial observation towards these issues, the team had come out with the Smart Band device. This device is wearable computer device in the form of strap band with a touchscreen interface used to monitor and detect the amount of UV and pH level that is exposed to our skin. Smart Band will display the UV measurement and help the users in applying the right amount and quantity of sunblock in daily basis through Smart Band apps. This Smart Band will display pH level of the rain too. Thus, people need to be aware on when to protect themselves from acid rain.